Role of Toll Like Receptor 4 in Alzheimer’s Disease - Calvo-Rodriguez, Maria; García-Rodríguez, Carmen; Villalobos, Carlos; Núñez, Lucía (Frontiers in Immunology, 2020)
Long-term evidence has confirmed the involvement of an inflammatory component in neurodegenerative disorders including Alzheimer’s disease (AD). This view is supported, in part by data suggesting protection provided by selected non-steroidal anti-inflammatory drugs (NSAIDs). Additionally, molecular players of the innate immune system have been recently proposed to contribute to these diseases. Toll-like receptors (TLRs) are transmembrane pattern-recognition receptors of the innate immune system that recognize different pathogen-derived and tissue damage-related ligands. TLR4 mediated signalling has been reported to contribute to the pathogenesis of age-related neurodegenerative diseases, including AD. Although the pathophysiology of AD is not clear, soluble aggregates (oligomers) of the amyloid β peptide (Aβo) have been proved to be key players in the pathology of AD. Among others, Aβo promote Ca2+ entry and mitochondrial Ca2+ overload leading to cell death in neurons. TLR4 has been recently involved in AD but the mechanisms are unclear. Our group recently reported that lipopolysaccharide (LPS), a TLR4 receptor agonist, increases cytosolic Ca2+ concentration leading to apoptosis. Strikingly, this effect was only observed in long-term cultured primary neurons considered a model of aging neurons, but not in short-term cultured neurons resembling young neurons. These effects were prevented significantly by pharmacological blockade of TLR4 receptor signalling. Moreover, TLR4 expression in rat hippocampal neurons increased significantly in aged neurons in vitro. Therefore, molecular patterns associated to infection and/or brain cell damage may activate TLR4 and Ca2+ signalling, an effect exacerbated during neuronal aging. Here, we briefly review the data regarding the involvement of TLR4 in AD.